Exploring the Diversity of Syllable Types: A Comprehensive Classification Framework (International Forum of Researchers and Lecturers, 2024)
This study aims to explore the diversity of syllable types and develop a comprehensive classification framework. Analysis was conducted on the syllable structures of various languages to understand both common patterns and language-specific variations in syllable formation. Linguistic data from diverse languages were collected and analyzed to identify phonotactic patterns, morphological interactions, prosodic features, and phonetic realizations of syllables. Findings indicate a wide range of syllable structures, ranging from simple CV to complex structures with multiple consonants and vowels. There are also significant interactions between syllable structure and morphological processes, as well as prosodic features. The results of this study are integrated into a comprehensive classification framework that encompasses various phonological, morphological, and phonetic dimensions of syllables. Theoretical and practical implications of the research are discussed, along with recommendations for future research.